The approaches, theories, models, frameworks, and methods in designing toolkits to support healthcare providers in health behaviour change: A scoping review protocol - Jillian Scandiffio; Ashvene Sureshkumar; Gregory Feng; Dina Gaid; Marina Wasilewski; Nicole Woods; Sarah Donkers; Robert Simpson; Sarah Munce (PLoS ONE, 2026)
Objective The scoping review aims to map the existing literature on the approaches, theories, frameworks, models and methods that have been used in the development of toolkits to support HCPs in health behaviour change. Introduction Lifestyle behaviours are associated with a range of health outcomes, including comorbidities, health utilization, and quality of life. Healthcare providers (HCPs) are key figures in supporting various clinical populations to change these behaviours but are often hindered by external factors. It is important to develop evidence-based tools that support the needs of HCPs for health behaviour change. Toolkits inform and provide guidance for HCPs to bridge the evidence to practice gap in a variety of areas, including health behaviour. However, there is a lack of information as to how these toolkits should be developed. This review aims to fill this gap by mapping the existing literature on how toolkits to support HCPs in health behaviour change have been developed. Methods This scoping review will follow the Joanna Briggs Institute (JBI) methodology and reporting will follow the Preferred Reporting Items for Systematic Reviews and Meta-analyses extension for scoping review (PRISMA-ScR). The search will be conducted across MEDLINE, Embase, Emcare, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Web of Science, and Scopus. Screening and data extraction will be conducted independently and in duplicate, with any disagreements resolved through discussion and involvement of a third reviewer. Data will be extracted from studies using a tool developed by the reviewers, guided by the JBI template. For synthesis, quantitative data will be reported descriptively and a conventional content analysis will be undertaken for qualitative data. Inclusion Criteria This scoping review will include studies published in peer-reviewed academic journals in English from any geographical area focusing on the development of a toolkit for HCPs involved in health behaviour change.